Multidimensional frailty and social participation in older adults during the Covid-19 pandemic - Venturini, Claudia (2022)
This study sought to identify the prevalence of multidimensional frailty in older adults referred by a Basic Health Unit in the city of Betim-MG and to analyze the association between frailty and social participation during the Covid-19 pandemic. An observational cross-sectional study was carried out with a random sample of 748 older adults. Most participants were considered frail and there was no association between multidimensional frailty and social participation.